Development of Flood Monitoring System - Damat, Nicodemus (2018)
Flood is a natural disaster that is no longer a surprise in Malaysia. Flood occurs for almost every year due to the monsoon season that happened twice a year in this country. Despite many alternatives and countermeasures taken by authorities in order to reduce the flood impacts, the number of evacuees and property damages is still high for every year. Therefore, more effort is required in order to develop a more effective flood monitoring system. In this project, a study on developing a flood monitoring system using Wireless Sensor Network (WSN) is being carried out. WSN is one of the reliable techniques that can be used to monitor the environmental physical condition. WSN has faster data transfer as well as accurate computation and cost effective. The system proposed in this project involves the development of flood monitoring system that consists of four major modules. The four major modules are sensing, communicating, data storing and alerting. Within the system, there will be two configuration of sensor nodes used to collect and transfer the data from monitoring site. Despite collecting and transferring data, sensor node also has a controller to control the input output of the data and to allow communication to be done wirelessly using Zigbee protocol. Three parameters which are water level, water flow rate, and rain precipitation will be monitored by the system. By having these three data, the system can use it to make decision and alert people on the condition of flood. As a result, all parameters were able to be measured and monitored. A notification and alert message were able to be sent to notify the administrator and affected people whenever the flood happen and reach alarming limit.